High energy Compton scattering, electronic structure and optical response of zirconium substituted lead titanate. (October 2022) - Joshi, Pooja K.; Mali, Deepika; Kumar, Kishor; Arora, Gunjan; Heda, N.L.; Ahuja, B.L.
Abstract: The electron momentum densities of PbTi1-x Zrx O3 (x = 0, 0.4 and 1) measured using high energy 137 Cs Compton spectrometer are reported. To validate the measurements, theoretical Compton profiles (CPs) and electronic structure of PbTi1-x Zrx O3 (x = 0, 0.4 and 1) are computed using the linear combination of atomic orbitals (LCAO) method. Differences between experimental and theoretical CPs unveil that the hybrid scheme (WC1LYP) is more applicable to account exchange and correlation energies in such materials than the other frequently used generalized gradient approximation (GGA) potentials. Experimental CPs based on scaling of equal-valence-electron-density show a more covalent character of PbTiO3 than that of PbTi0.6 Zr0.4 O3 and PbZrO3, which is in consonance with the present LCAO based Mulliken's population charge reorganization data. The density of states, dielectric constants, frequency-dependent absorption spectra and refractive indices are computed using the modified Becke-Johnson potential as incarnated in the full-potential augmented plane wave method. The present optical response suggests the possibility of using PbTi1-x Zrx O3 in the device for ultra-violet detection. Highlights: Compton profiles (CPs) of PbTi1-x Zrx O3 measured using 137 Cs Compton spectrometer. Uniquely compared measured CPs with LCAO data to suggest quantum models. Explored nature of bonding in PbTi1-x Zrx O3 using CPs and LCAO-MP data. Reported optical response and found use of materials in detection of UV-rays.